Practice of Buying and Selling Grain With Deferred Payment According to Islamic Law in Rantau Badauh District - Ni'mah, Mudawamatun (Sharia Journal and Education Center Publishing, 2024)
Abstract The background of this research is that buying and selling in accordance with Islamic law must avoid what is forbidden, such as avoiding elements of gharar or uncertainty which can cause losses between one of the parties. In its development, apart from buying and selling in cash, buying and selling is also done in a tough manner. In the Rantau Badauh community, some people buy and sell grain using a deferred payment method, while the priority is handing over the grain to the buyer. However, the price and payment time are not specified at the beginning of the agreement. The problem in this research is the practice of buying and selling grain with deferred payment in Rantau Badauh District and how Islamic law reviews the practice of buying and selling grain with deferred payment. Keywords: Buying and selling, Grain, Deferred payment Abstrak Latar belakang penelitian ini adalah jual beli yang sesuai dengan syariat Islam harus menghindari apa yang diharamkan, seperti menghindari unsur gharar atau ketidakpastian yang dapat menimbulkan kerugian antara salah satu pihak. Dalam perkembangannya, selain jual beli secara tunai, jual beli juga dilakukan dengan cara tangguh. Pada masyarakat Rantau Badauh, sebagian masyarakat melakukan jual beli gabah dengan cara pembayaran ditangguhkan, yang diutamakan adalah penyerahan gabah kepada pembeli. Namun, harga dan waktu pembayaran tidak ditentukan di awal perjanjian. Permasalahan dalam penelitian ini adalah bagaimana praktik jual beli gabah dengan pembayaran ditangguhkan di Kecamatan Rantau Badauh dan bagaimana tinjauan hukum Islam terhadap praktik jual beli gabah dengan pembayaran ditangguhkan. Kata Kunci: Jual Beli, Gabah, Pembayaran Ditangguhkan